Effect of frother concentration on bubble trailing vortex characteristics and particle entrainment in flotation - ZHU Jinbo; SHI Qinghui; ZHU Hongzheng; HE Hailing; QIN Zhiqian; ZHANG Yong; PAN Gaochao (Meitan kexue jishu, 2023)
To investigate the effect of frother concentration on bubbles and their tail vortex zone characteristics in flotation is an important prerequisite for predicting the probability of particle coiling in the trailing vortex zone of flotation bubbles. The flow field characteristics of the bubble trailing vortex region under different sec-octyl alcohol (2-octanol) foaming agents were studied by the laboratory homemade proposed rising bubble device and particle image velocimetry system. The fluid separation behavior of the bubble surface and the trailing vortex height characteristics were analyzed. The morphological characteristics of the bubbles and the trajectory and distribution probability of the particles in the bubble wake area were observed with the high-speed camera system. The results of the research are as follows: The size of bubbles slightly decreases and the aspect ratio gradually increases with the increase of the frother concentration. The boundary layer separation angle of the bubbles gradually increases with the increase of the frother concentration, and there is a critical separation angle of 196.70°. The vortex caused by the bubble is mainly concentrated in the region where the flow velocity is less than 0.09 m/s. The height of the vortex area gradually decreases with the increase of the frother concentration, and the critical value of the minimum vortex area is 1.06 times the bubble diameter. There are three kinds of trajectories of particles in the bubble trailing vortex area, and the trajectory of particle coiling can be divided into three significant stages, and the force on the particles is the critical factor leading to the difference in their coiling types. The range and probability of particles being coiled gradually decreased with the increase of frother concentration. The critical concentration affecting both the bubble trailing vortex and particle motion was 1.6×10-4 mol/L. The results of the study clarified the mechanism of frother concentration on mineral particle entrainment in the bubble trailing vortex and provided valuable guidance for the development of microfine mineral flotation technology.